Law librarians and collective intelligence - de Sousa, Regina Celi; Napoleone, Luciana Maria (Qualitative and Quantitative Methods in Libraries, 2019)
Analysis on historic compilation of events on legal information and documentation in Brazil, conducted through an exploratory and qualitative systematic study. A bibliographic research on collective intelligence, related to librarianship and information science, was combined to questionnaire with outstanding professionals and leaderships of Brazilian legal information and documentation area. Three moments identified are represented by three distinct events (ENBJ: 1971-1994, ENDIJ: 1984-2000, SNDIJ: 2007-2013), which have their analysis detailed in the context of Law Librarianship. Finally, the interrelation of the Law librarians and the collective intelligence is discussed